Cervical squamous and glandular intraepithelial neoplasia: identification and current management approaches - Wright V Cecil (Instituto Nacional de Salud Pública, 2003)
Certain types of human papillomaviruses (HPV) are associated with squamous intraepithelial lesions and cancer and these are termed high-risk. HPV type 16 is detected in approximately half of the high-grade squamous intraepithelial lesions and cancer. Because of the high rate of spontaneous regression of low-grade squamous lesions, follow-up by cytology, colposcopy and possible biopsy appears preferable. Due to the higher rate of progression to malignancy of the high-grade lesions conservative treatment is recommended. One of the most common reasons for persistence relates to the human immunodeficiency virus. Adenocarcinoma in situ is an uncommon disorder and not well identified by cytologic sampling or colposcopic inspection. The diagnosis is made by cone biopsy, the specimen having negative margins for disease. Hysterectomy is the treatment procedure of choice unless fertility is an issue. Excisional methods (particularly electrosurgical loop) can interfere with accurate histological interpretation in some cases of both squamous disease and adenocarcinoma in situ.